Clinical researchCord blood resistin and adiponectin in term newborns of diabetic mothers - Mohamed, Maha H.; Gad, Ghada I.; Ibrahim, Hala Y.; El Shemi, Mohamed S.; Moustafa, Mohamed F.; Atef, Shereen H.; Ramadan, Naglaa M.; El Saeid, Shimaa M. (Archives of Medical Science, 2010)
Introduction : Adipose tissue can release hormones into the blood stream in response to specific extracellular stimuli or changes in metabolic status. Resistin, an adipose-secreted factor, is primarily involved in the modulation of insulin sensitivity and adipocyte differentiation. Adiponectin, an adipocyte-specific hormone with insulin sensitizing, anti-inflammatory and anti-atherogenic effects, is reduced in obesity and type II diabetes. The aim of the study was to assess the influence of maternal pre-existing diabetes on cord blood resistin and adiponectin at birth in relation to neonatal anthropometric parameters and cord blood insulin levels. Material and methods: A total of 60 term newborns were prospectively enrolled and categorized into three groups: 20 were macrosomic infants of pre-gestational diabetic mothers (group I), 20 were non-macrosomic infants of pre-gestational diabetic mothers (group II) and 20 were healthy non-macrosomic infants born to non-diabetic mothers serving as controls (group III). Infants’ anthropometric indices were recorded. Cord blood samples for glucose, insulin, resistin and adiponectin assay, together with maternal glycosylated haemoglobin were obtained. Results: Serum insulin was increased while resistin and adiponectin were significantly decreased in infants of diabetic mothers (IDMs) compared to the control group. Serum glucose, insulin, resistin and adiponectin were comparable in group I and II. Cord serum resistin correlated positively with cord blood glucose in IDMs in both macrosomic and non-macrosomic groups. Cord serum insulin correlated positively with triceps skinfold thickness in all studied neonates. Cord serum resistin and adiponectin showed no correlation with neonatal anthropometric indices. Multiple regression analysis demonstrated that insulin, resistin and adiponectin together were highly correlated with birth weight, with adiponectin as the one responsible for this positive correlation. Conclusions: Infants of diabetic mothers had elevated levels of cord serum insulin and suppressed levels of cord serum resistin and adiponectin, suggesting that the regulation of these metabolic pathways is probably operational before birth. Levels were comparable in both macrosomic and non-macrosomic neonates.